A comparative tunnelling network approach to assess interspecific competition effects in termites - Jost, C.; Haifig, Ives [UNESP]; de Camargo-Dietrich, C. R. R. [UNESP]; Costa-Leonardo, A. M. [UNESP] (Springer Basel Ag, 2012)
We study the tunnelling network dynamics of two morphologically and ecologically very similar native termite species from the Brazilian Cerrado, Cornitermes cumulans and Procornitermes araujoi, both when they are digging alone or when their tunnel networks can meet. Their network topologies have the same geometrical properties with only slight differences in digging speed and branching rates. Petri dish laboratory assays show that the two species have a strong potential for interference competition. However, encounters between the two tunnelling networks produce no measurable effect on the level of the total network growth dynamics. A brief fighting erupts in the meeting zone with some increased mortality and territorial gains or losses on both sides. This aggressive encounter is quickly ended by walling off the gap between the two networks. Tunnel speed analysis of the last 5 mm before an encounter shows some evidence that at least one species, P. araujoi, detects the presence of the competitor even before actually breaking into their tunnels. We compare these results to those found in invasive termite species and discuss them in the species' ecological context: their strategies might be linked to the well-known r- and K-strategy concept.
Keywords: Termites; Tunnelling behaviour; Network topology; Interspecific competition; Cornitermes cumulans; Procornitermes araujoi